Distribution, transformation and toxicity evaluation of 2, 6-Di-tert-butyl-hydroxytotulene in aquatic environment. (December 2019) - Wang, Yan; He, Lin; Lv, Guochun; Liu, Wen; Liu, Jiashuo; Ma, Xiaohui; Sun, Xiaomin
Abstract: 2, 6-Di-tert-butyl-hydroxytotulene (BHT), as a significant synthetic phenolic antioxidant (SPA), has received increasing attention in the environmental field. In the present study, the BHT is confirmed to be mainly distributed in the liquid phase in the environment base on the Aspen PLUS simulation results. The mechanism and kinetics of BHT transformation initiated by OH radicals were conducted in aquatic environment using density functional theory (DFT) method. Briefly, seven initiation reactions and three detailed transformation pathways of BHT were reported. The H atoms in the t-butyl and methyl group were found more favorable to be abstracted. The C1 site of the BHT was susceptible to addition by OH radicals. Rate constants of different initial reactions were calculated and they were inhibited by temperature rise. Meanwhile, the acute and chronic toxicities of BHT and its metabolites were evaluated at three different trophic levels using the ECOSAR program. During the degradation process, the toxicities of these metabolites gradually decreased, but the toxicities of the final product 2, 6-di-tert-butyl-2, 5-cyclohexadien-1, 4-dione (BHT-Q) were significantly increased. These results could help to reveal the transformation mechanism and risk assessment of BHT in aquatic environment, and further design the experimental and industrial applications of SPAs. Graphical abstract: Image 1 Highlights: Aspen PLUS simulation was used to clarify that more than 90% of the BHT in the environment exist in liquid phase. This study demonstrated that BHT was more easily oxidized on p-methyl group to generate metabolites. The product BHT-Q has strong toxicity to aquatic ecosystem. Abstract : BHT is easily oxidized by OH radicals in aquatic environment to form BHT-CHO, BHT-Q and other metabolites that are more harmful to the aquatic environment.